HASHTAGS, HIERARCHIES AND HEGEMONIES: MAINSTREAM DIGITAL FEMINIST ACTIVISM AND INTERSECTIONAL CRITIQUES - Fox, Izzy E (AoIR Selected Papers of Internet Research, 2023)
This paper focuses on the digital-material hybridity of the contemporary feminist activist, particularly the problematic and progressive potential offered by the technological affordances of the Internet and digital social media. In addition, the paper highlights the associated anxieties for feminists of being online and engaging in what is often, in this “age of surveillance capitalism” (Zuboff 2019) and toxic masculinity, a hostile, commodified and misogynistic milieu. Furthermore, the digital affordances enabled through the proliferation of Web 2.0 technology inform the nature of feminist online discourse and campaigning, which has, at times, contributed to the moral panic that surrounds attempts at centering marginalized voices, particularly members of the trans community and sex workers.The paper will explore the relationship between online tools and platforms adopted by mainstream contemporary feminists and the role they have played in constructing ‘othering’ hierarchies within feminism, as well in enabling the intersectional critique of these narratives. Avoiding either cyber-utopian or dystopian arguments, or a techno-determinist or utilitarian stance, this paper accounts for the complex and contradictory environment that the Internet offers to feminism. The paper also recognizes the enmeshed nature of feminists with their digital tools and platforms as well as the problematic and progressive feminist activism taking place online.